Nepticulidae (Lepidoptera) of East Asia (1). Re-examination of the male genitalia of types deposited at the Russian Academy of Sciences - Stonis, Jonas R.; Rocienė, Agnė (Zootaxa, 2013)
East Asia is famous for its tremendous overall biodiversity, and the Nepticulidae are no exception. The majority of the currently known fauna of Nepticulidae was described in 1984–1987 by several authors, but R. Puplesis is the author of the largest number of new species from the region. Unfortunately, the genitalia of all species from Primorskiy Kray, Sakhalin, and the Kuril Islands were described from temporary slides in glycerol, and therefore, the drawings do not always show all details of genital armature or may be confusing. Without the baseline data providing morphology of genital armature of type material, it is impossible to continue studies on the East Asiatic fauna of Nepticulidae. In this paper we reexamine and document for the first time with photographs the types of 56 species described by R. Puplesis from the Russian Far East. Details of the morphology is updated for most of the re-examined species.